Identifying Permanently Disabled Workers with Disproportionate Earnings Losses for Supplemental Payments - Seth A. Seabury, Ethan Scherer (RAND Corporation, 2014)
In September 2012, the State of California adopted Senate Bill 863, a sweeping reform of the stateâ€™s workersâ€™ compensation system. The goal of the bill was to contain medical costs for injured workers while restoring some of the permanent disability benefits that had been lost from previous reform efforts. The bill made many changes to the disability benefit system, one of which was the creation of a â€œreturn-to-work program.â€ This program, which is to be funded at $120 million per year, would provide supplemental payments to injured workers whose permanent disability benefits are disproportionately low in comparison to their earnings loss. The bill provided the Director of the Department of Industrial Relations (DIR) wide leeway in the design and implementation of the program. In addition, the bill required the Director, in consultation with the California Commission on Health and Safety and Workersâ€™ Compensation (CHSWC), to determine eligibility and the amount of payments to be made based on a study. This study, funded by CHSWC, represents RANDâ€™s efforts to help DIR and CHSWC in developing a methodology for the eligibility determination and benefit amounts for the new Return-to-Work program. This work builds on many previous RAND efforts to help CHSWC, DIR, and the State of California improve the adequacy and efficiency of the workersâ€™ compensation system through research and analysis